Development and Validation of Scientific Inquiry Literacy Instrument (SILI) Using Rasch Measurement Model - Dina Rahmi Darman; Andi Suhandi; Ida Kaniawati; Achmad Samsudin; Firmanul Catur Wibowo (MDPI AG, 2024)
This research aims to develop an instrument of knowledge and skills called the Scientific Inquiry Literacy Instrument (SILI). Instrument measurement analysis uses the Rasch model by utilizing the Winsteps application. This research uses mixed methods research that combines interviews as qualitative research and tests as quantitative research. The research design used is Sequential Exploratory. The SILI contains 28 knowledge aspect indicators and 37 skills aspect indicators. Based on the Outfit mean square (MNSQ), Z-Standard value (ZSTD), and point measure correlation value (Pt Mean Corr), it was obtained that the three aspects of the SILI meet the criteria for an acceptable item in the Rasch measurement model. Based on item analysis biased towards gender, region, and science major, all SILI items in knowledge and skills meet the probability criteria > 0.05, so all items can be used without harming one group. The findings of the research dimensionality of the SILI for aspects of knowledge and skills are 26.9% and 20.4%. Thus, all aspects of the SILI can measure what should be measured and fulfill all the criteria for items accepted based on the Rasch model for measuring science inquiry literacy.